2020
DOI: 10.20524/aog.2020.0470
|View full text |Cite
|
Sign up to set email alerts
|

Decreased risk of hepatocellular carcinoma recurrence with directacting antivirals compared with no treatment for hepatitis C: a meta-analysis

Abstract: Background Studies investigating the association between direct-acting antivirals (DAAs) and the recurrence of hepatocellular carcinoma (HCC) related to hepatitis C (HCV) have yielded conflicting results. The objective of this meta-analysis was to define the short-and long-term recurrence rates of HCC after DAA treatment.Methods A search of multiple databases was performed, including Scopus, Cochrane, MEDLINE/ PubMed and abstracts from gastroenterology meetings. Only studies reporting the recurrence of HCC in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 27 publications
4
15
1
Order By: Relevance
“…Notably, the non-responsiveness of this patient was not seen by HCV RNA load, ALT or serological fibrosis scores. The success of viral eradication in other studies has been reported, similarly to the present study, as being about 93% [ 10 , 13 , 56 ]. Thus, there is a need to identify those patients who will not respond to DAA therapy early, so that their therapy can be changed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Notably, the non-responsiveness of this patient was not seen by HCV RNA load, ALT or serological fibrosis scores. The success of viral eradication in other studies has been reported, similarly to the present study, as being about 93% [ 10 , 13 , 56 ]. Thus, there is a need to identify those patients who will not respond to DAA therapy early, so that their therapy can be changed.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, immunosuppression commonly applied to KTRs could also lead to a high risk of HCV reactivation and recurrence, resulting in the progression of hepatic fibrosis and, ultimately, a high incidence of liver cirrhosis and hepatocellular carcinoma [ 8 , 9 ]. Direct-acting antiviral agents (DAAs) are very effective in viral eradication, decreasing the risk of hepatocellular carcinoma [ 10 , 11 , 12 , 13 ]. As they are very effective in HCV therapy [ 14 , 15 , 16 , 17 ], DAAs are recommended by the current Kidney Disease Improving Global Outcomes (KIDGO) guidelines for treating HCV-infected patients with renal disease [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…We further stratified our study cohort based on the viral infection status. Multivariate analysis also revealed the treatment of HBV (HR, 0.601; 95% CI, 0.441–0.818; p = 0.001) and HCV (HR, 0.467; 95% CI, 0.328–0.664; p<0.001) are good independent factor for RFS in each group, the same results as previous study [ 32 34 ].…”
Section: Discussionsupporting
confidence: 86%
“…After variable adjustments, the study reported that DAA exposure is not associated with an increased risk of HCC recurrence (HR = 0.90; 95%CI: 0.70-1.16)[ 60 ]. A meta-analysis published by Lui et al [ 61 ] also showed that the use of DAA therapy is associated with a significantly lower risk of HCC development compared to patients without DAA treatment. The authors found a > 60% lower risk of HCC recurrence in patients exposed to DAA compared to controls (OR = 0.36, 95%CI: 0.27-0.47; P < 0.001; I 2 = 88%).…”
Section: Hcc Recurrence After Daa Therapymentioning
confidence: 99%
“…In addition, a large comparative study from Japan revealed that posttreatment Wisteria floribunda agglutinin positive Mac-2 binding protein (WFA + M2BP) was significantly associated with HCC recurrence in patients with HCV without advanced liver fibrosis. In addition, the comparative study for occurrence and recurrence of HCC in IFN-based vs DAAs, showed that AFP (> 5.4 ng/mL) and WFA + M2BP levels (> 1.8 COI) were strongly associated with de novo HCC in those with DAA therapy[ 61 ]. In a recently published retrospective study, Sangiovanni et al [ 47 ] found at multivariable Cox regression models that ascites and AFP log-value were independently associated with HCC occurrence, while a history of alcohol abuse and HCC recurrence was associated with HCC recurrence.…”
Section: Risk Factors For De Novo and Recurrent Hcmentioning
confidence: 99%